A Comprehensive Study of Renewable-Powered Floating Oil Skimmer Design for Indonesian Oil Spill Recovery - Yasim, Ahmad; Irsan, Muhammad; Dwiprayuda, Marfiansyah Nasra; Ikhsan, Muh.; Zulkifli, Muh. Fadil (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2026)
Indonesian waters have intense shipping and offshore oil industry activities, often resulting in marine pollution from oil spills. These spills damage marine ecosystems, disrupt sea transportation, cause organism mortality and migration, and reduce fishery production as well as marine tourism. To mitigate oil pollution, oil skimmers are widely used. However, their current applications mostly rely on generator-based electric power and are limited to land-based industrial environments. This study aims to develop a floating oil skimmer powered by renewable energy for marine oil spill recovery, utilizing the abundant solar and wind resources available at sea. The research employs a design-based approach combined with model testing to enhance the accuracy of calculation inputs. The results indicate that the barge-type platform provides optimal performance due to its high buoyancy, low resistance, and good stability and seakeeping characteristics. The oil skimmer integrates a corrugated plate interceptor (CPI) separator to accelerate the oil–water separation process. Two 100 Wp solar panels supply electrical power stored in two 12 V, 32 Ah hybrid batteries, which operate an oily water pump, a DC 775 motor for the skimmer drum, and a cooling system pump to prevent component overheating. Experimental results show the highest efficiency at 120 RPM, with an average oil recovery rate of 2.2 mL per revolution, equivalent to 15.84 L/h or 380.16 L/day. Further improvements are recommended by optimizing the skimmer material, adjusting its position, refining the oil scraper, and adding an oil skimmer unit in Chamber 1.